Clinicopathological significance of perineural and lymphovascular invasion in oral and oesophageal squamous cell carcinoma: a retrospective study - George, Anita; Sheikh, Mahrukh; Bukhari, Uzma; Zafar, Syeda Sadia; Bokhari, Samra; Azhar, Ramsha (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the presence and association of perineural and lymphovascular invasion with different stages of oral and oesophageal squamous cell carcinoma, and to assess their relationship with lymph node metastasis in both types of tumours. Method: The retrospective study was conducted from December 1, 2023, to April 1, 2024, at the Department of Histopathology, Dow Diagnostic Research and Reference Laboratory, Dow University of Health Sciences, Karachi, and comprised diagnostic reports of histopathology along with haematoxylin and eosin slides of patients diagnosed with oral squamous cell carcinoma and oesophageal squamous cell carcinoma from June 1, 2022, to June 1, 2023. Data ws compared to explore the association of perineural and lymphovascular invasion with tumour stage and nodal metastasis. Data was analysed using SPSS 26. Results: Of the 100 cases, 60(60%) had oral squamous cell carcinoma, with 41(68.3%) being males and 35(58.3%) being aged >40 years. There were 40(40%) cases with oesophageal squamous cell carcinoma, with 28(70.2%) being males and 27(68.4%) being aged >40 years. Among the oral cases, perineural invasion (p<0.001) and lymphovascular invasion (p=0.05) were significantly associated with nodal metastasis. Depth of invasion was significantly associated with both perineural (p=0.024) and lymphovascular (p=0.047) invasion. Tumour size was significantly associated with perineural invasion (p=0.05), but not with lymphovascular invasion (p=0.227). Among the oesophageal squamous cell carcinoma cases, a significant association was identified for tumour stage with perineural invasion (p=0.047) and lymphovascular invasion (p-0.006). Perineural invasion (p=0.002) and lymphovascular invasion (p<0.001) were significantly associated with nodal metastasis. Conclusion: Perineural and lymphovascular invasion showed potential as diagnostic and therapeutic targets for managing oral squamous cell carcinoma and oesophageal squamous cell carcinoma. Key Words: OSCC, ESCC, Perineural invasion, Lymphovascular invasion.